The Progress of Emergency Medicine in Taiwan, China, and Hong Kong: Perspective from Publications in Emergency Medicine Journals, 1992–2011. (23rd February 2014) - Lee, Ching-Hsing; Chaou, Chung-Hsien; Lin, Chih-Chuan
Abstract : Study Objective . The progress of emergency medicine (EM) in Taiwan, China, and Hong Kong was evaluated from the perspective of publications in EM journals. Methods . This was a retrospective study. All articles published from 1992 to 2011 in all journals in the EM category in the 2010 Journal Citation Reports (JCR) were included. A computerized literature search was conducted using the SciVerse Scopus database. The slope ( β ) of the linear regression was used to evaluate the trends in the numbers of articles as well as the ratios to the total number of EM journal articles. Results . The trends in the numbers of articles from Taiwan, China, and Hong Kong were 6.170, 1.908, and 2.835 and the trends in the ratios of their publication numbers to the total number of EM journal articles were 15.0 × 10 −4, 4.60 × 10 −4, and 6.80 × 10 −4, respectively. All P -values were <0.01. The mean, median, and 75th percentiles of the number of citations in all EM journals were greater than those of these three areas. Conclusions . The publications from Taiwan, China, and Hong Kong have increased at a higher rate than those of the overall EM field in the past 20 years and indicated the rapid progress in these three areas.